Attitudes and Perceptions of Health Protection Measures Against the Spread of COVID-19 in Italy and Poland - Lorettu, Liliana; Mastrangelo, Giuseppe; Stepien, Joanna; Grabowski, Jakub; Meloni, Roberta; Piu, Davide; Michalski, Tomasz; Waszak, Przemyslaw M.; Bellizzi, Saverio; Cegolon, Luca (Frontiers in Psychology, 2021)
Background. During the first wave of COVID-19 pandemic (April- May 2020), 6,169 Polish and 939 Italian residents were surveyed with an online questionnaire investigating socio-demographic information and personality traits (1st section) as well as attitudes, position and efficacy perceptions on the impact of lock down (2nd section) and various health protection measures enforced (3rd section). Methods. The “health protection attitude score” (HPAS), an endpoint obtained by pooling up the answers to questions of the 3rd section of the survey tool was investigated by multiple linear regression models, reporting regression conefficients (RC with 95% confidence intervals (95%CI). Results. Concerns for business and health due to COVID-19 were associated with a positive attitude towards risk reduction rules. By contrast, male sex, concerns about reliability of information available online on COVID-19 and its prevention, along with the feeling of not being enough informed on the transmissibility/prevention of SARS-CoV-2 were associated with a nega-tive attitude towards risk mitigation measures. Discussion. A recent literature review identiﬁed two social patterns with different features in relation to their attitude to-wards health protection rules against the spread of COVID-19. Factors positively associated with adherence to public health guidelines were perceived threat of COVID-19, trust in government, female sex and increasing age. Factors associated to de-creased adcompliance were instead underestimation of the COVID-19 risk, limited knowledge of the pandemic, belief in con-spiracy theories and political conservativism. Very few studies have tested interventions to change attitudes or behaviors. Conclusions. To improve attitude and compliance towards risk reduction norms, a key intervention is fostering education and knowledge on COVID-19 health risk and prevention among the general population. However, information on COVID-19 epidemiology might be user-generated and contaminated by social media, which contributed to create an infodemic around the disease. To prevent the negative impact of social media and to increase adherence to health protection, stronger content control by providers of social platforms is recommended.